COVID-19 Lung Damage in a Preterm Newborn - Khalouaoui, Amal; Habert, Paul; Dequin, Marion; Gire, Catherine; Tosello, Barthélémy (Journal of Pediatric Infectious Diseases, 2022)
The new coronavirus disease 2019 (COVID-19) was declared responsible for a global pandemic by the World Health Organization (WHO) on March 11, 2020. It created, since its emergence, a special concern in neonates given their immature immune system and their frequent contact with caregivers.Monochorionic very preterm female neonate (315/7 weeks of gestation) with growth retardation had at 3 weeks of age severe lung damage following an acute respiratory failure caused by horizontally transmitted severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pneumonia. Before this acute episode, she was without respiratory support apart from 7 days of positive airway pressure following a respiratory distress syndrome. Both of her parents, her twin sister, and her referent nurse tested positive for SARS-CoV-2. Chest radiographs showed bilateral alveolar infiltration. Chest computed tomography (CT) scan detected multiple ground-glass opacifications in both lungs along with ventilation disorders and bronchial wall thickening. Neonate paraclinical tests showed a negative C-reactive protein and hypogammaglobulinemia. Mechanical ventilation was needed for 1 week along with sedation, pharmaceutically induced paralysis, and inhaled nitric oxide. Severe bronchopulmonary dysplasia revealed by oxygen dependency at 36 weeks of gestation was treated with steroids and noninvasive respiratory support. The neonate was discharged with free oxygen at home.Her twin sister, also SARS-CoV-2–positive, only needed noninvasive ventilation for 19 days.Severe forms of COVID-19 in premature neonates, with long-term respiratory sequelae, are possible. Considering the lack of data in this age group, more studies are needed to investigate the risk factors associated with severe symptoms, the effects of specific treatments, and the long-term prognosis of the disease.
Keywords: coronavirus disease 2019; respiratory distress syndrome; preterm infant